2008
DOI: 10.1002/ijc.23857
|View full text |Cite
|
Sign up to set email alerts
|

A panel of p16INK4A, MIB1 and p53 proteins can distinguish between the 2 pathways leading to vulvar squamous cell carcinoma

Abstract: Two pathways leading to vulvar squamous cell carcinoma (SCC) exist. The expression of proliferation-and cell-cycle-related biomarkers and the presence of high-risk (hr) HPV might be helpful to distinguish the premalignancies in both pathways. Seventy-five differentiated vulvar intra-epithelial neoplasia (VIN)-lesions with adjacent SCC and 45 usual VIN-lesions (32 solitary and 13 with adjacent SCC) were selected, and tested for hr-HPV DNA, using a broad-spectrum HPV detection/genotyping assay (SPF 10 -LiPA), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
60
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 43 publications
(77 reference statements)
3
60
0
Order By: Relevance
“…In general, several studies showed that patients with uVINrelated vulvar SCC are younger than dVIN/LS-related vulvar SCC patients (Hording et al, 1994;Hampl et al, 2006;Hoevenaars et al, 2008;van de Nieuwenhof et al, 2009a). In our study, we confirm this observation with a significant difference in age distribution between the two different groups, 72 years for the hrHPVunrelated and 54 years for the hrHPV-related groups (Po0.001).…”
Section: Discussionsupporting
confidence: 87%
“…In general, several studies showed that patients with uVINrelated vulvar SCC are younger than dVIN/LS-related vulvar SCC patients (Hording et al, 1994;Hampl et al, 2006;Hoevenaars et al, 2008;van de Nieuwenhof et al, 2009a). In our study, we confirm this observation with a significant difference in age distribution between the two different groups, 72 years for the hrHPVunrelated and 54 years for the hrHPV-related groups (Po0.001).…”
Section: Discussionsupporting
confidence: 87%
“…8,12 In addition, despite the fact that differentiated VIN was first described in the 1960s by Abell 23 as a highly differentiated form of vulvar carcinoma in situ, until more recently, the entity has not gained wide attention because its existence as a clinicopathological entity has long been questioned. 18 As more insight is gained that vulvar squamous cell carcinomas originate from two different pathways, each with its own premalignant lesions, 24,25 differentiated VIN has been designated the direct precursor of the HPV-independent pathway. Earlier, all VIN lesions were classified as being HPV related, which explains the high incidence of lichen sclerosus with HPV-induced lesions, which turned out to be differentiated VIN instead of the nowadays socalled usual VIN lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Full or near full thickness p16 INK4A immunostaining characterizes most classic VINs, but normal and hyperplastic vulvar epidermis, lichen sclerosus, and differentiated VIN are usually p16 negative. 17,18 Presence of strongly p53-positive suprabasal cells was proposed as an aid for the diagnosis of differentiated VIN 20 but this marker is not considered highly sensitive. Independent studies found a range of 54 to 83% of differentiated VINs to have abnormal p53 immunostaining patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Independent studies found a range of 54 to 83% of differentiated VINs to have abnormal p53 immunostaining patterns. 9,17,20,37,38 The fact that p53 is detected only in some differentiated VIN lesions might be explained by differences in the type of TP53 gene mutation, with strong p53 immunostaining associated with dominant-negative missense mutations and absence of staining associated with TP53 deletions. 9 Weak basal layer p53 staining has been reported in some lichen simplex chronicus and lichen sclerosus lesions in the absence of basal atypia and not associated with carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation